Novel epitheliomesenchymal biphasic stomach tumour (gastroblastoma) in a 9-year-old: morphological, usltrastructural and immunohistochemical findings. Issue 3 (4th March 2010) - Shin, Dong Hoon; Lee, Jung Hee; Kang, Hyun Jeong; Choi, Kyung Un; Kim, Jee Yeon; Park, Do Youn; Lee, Chang Hun; Sol, Mee Young; Park, Jae Hong; Kim, Hae Young; Montgomery, Elizabeth
Abstract : Gastroblastoma is a rare gastric epitheliomesenchymal biphasic tumour composed of spindle and epithelial cells, reported by Miettinen et al in a series of three cases in 2009. All those cases arose in stomachs of young adults. Neither the epithelial nor the mesenchymal component displayed sufficient atypia to diagnose a carcinosarcoma or other malignancy. On immunohistochemistry, the epithelial component expressed cytokeratin, and the mesenchymal component was positive for vimentin and CD10. Miettinen et al designated these neoplasms as gastroblastomas based on their similarities with other childhood blastomas such as pleuropulmonary blastoma and nephroblastoma. This report describes a probable fourth case of this unique type of neoplasm. The present case arose in the gastric antrum of a 9-year-old boy. While similarities were evident with the other cases, there were some differences. The epithelial component was more predominant and showed more mature morphology. Immunohistochemically, the epithelial component showed immunolabelling for c-KIT and CD56. The mesenchymal component was only focally positive for CD10. Ultrastructually, desmosomes and microvilli were found supporting a truly epithelial lesion.